Reconstruction of body height from measurements of long bones - Gralla, Gertruda (Anthropological Review, 1976)
On the grounds of living persons measurements (300 males and 500 females from Poland) the author has computed moment-product coefficients of correlation between body height and the lenght of humerus, radius, femur and tibia. Afterwards regression equations were given together with a special table as a convenient mean for reconstructing body heigth of modern Polish people from measurements of long bones.